2009
DOI: 10.4314/aga.v17i3.1670
|View full text |Cite
|
Sign up to set email alerts
|

Forms and contents of iron and aluminum in inland flood plains of South-Eastern Nigeria

Abstract: Fourteen representative soils from inland flood plains in Southeastern Nigeria were studied to characterise forms (crystalline and amorphous) contents in iron and aluminium oxides. Total iron and aluminium, extracted using HCI after fusion with Na 2 CO 3 , ranged from 1.25 to 7.74 % by weight of dry soil, with a mean of 3.29 % for total Fe 2 O 3 and from 9.75 to 44.67 % with a mean of 26.04 % for total Al 2 O 3 . Broad textural grouping of the soils showed mean total contents of Fe 2 O 3 and Al 2 O 3 comparabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 8 publications
3
6
1
1
Order By: Relevance
“…Statistically, there was no significant difference (P < 0.05) in oxalate Al mean among the three wetland soil types studied. This result is in tandem with the low mean Alo values (0.02 -0.09%) of some floodplain soils of Southeastern Nigeria (Ibia, 2005). The mean values of Alo in the three wetland soils were greater than the mean Ald indicating the prevalence of amorphous Al in these soils than the crystalline Al which confirms that the soils are relatively less weathered and more reactive.…”
Section: Aluminium Oxidessupporting
confidence: 67%
“…Statistically, there was no significant difference (P < 0.05) in oxalate Al mean among the three wetland soil types studied. This result is in tandem with the low mean Alo values (0.02 -0.09%) of some floodplain soils of Southeastern Nigeria (Ibia, 2005). The mean values of Alo in the three wetland soils were greater than the mean Ald indicating the prevalence of amorphous Al in these soils than the crystalline Al which confirms that the soils are relatively less weathered and more reactive.…”
Section: Aluminium Oxidessupporting
confidence: 67%
“…Therefore, grain aluminum (Al) levels have largely been used to identify genotypes that are contaminated (Stangoulis and Sison, 2008). Al is even more abundant in soil than the Fe level (Ibia, 2002;Rauch and Pacyna, 2009) but is not found in clean plant tissue and is easily analyzed by ICP-OES, it can be used as an indicator of soil contamination. Typically, soil contamination of grain is considered to be acceptably low in grain analysis reports where Al is present at <5 mg kg −1 (Pfeiffer and McClafferty, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst landscapes, best bulk soil Fed was at the downslope while Feox and Feox/Fed were at the upslope positions. Generally, Fed was higher than Feox, giving low Feox/Fed ratio (0.04-0.17) and indicating high crystallinity and good drainage (Udo, 1980;Ibia, 2001). It has been noted that Feox/Fed ratio or iron activity is useful in evaluating the age, drainage conditions, degree of weathering and amounts of crystalline or free amorphous oxides in soils (Blume and Schwertmann, 1969;Alamdari et al, 2010).…”
Section: Sesquioxide Concentrations In the Soilsmentioning
confidence: 99%
“…Reactivity of sesquioxides is also associated with the ratio or relative amounts of the poorly ordered and the crystalline Fe and Al oxide fractions in soils (Hassan et al, 2005). Research has indicated that poorly drained soils have high ratios and thus more reactive than the well-drained soils (Ibia, 2001).…”
Section: Introductionmentioning
confidence: 99%